Critical Path Analysis Using Microsoft Project 2016 on the Implementation Schedule of Residential House Construction Projects - Muhammad Tahrir; Fajar Ramadhani; Dewi Astuti Baco (TEPIAN, 2023)
A project requires good planning, careful execution and effective and efficient use of resources. The implementation of the development of a construction project consists of a series of activities that are interrelated with one another. This is where the importance of planning and scheduling projects properly to facilitate implementation in the field and development can be completed on time according to schedule. The existence of obstacles or obstacles that will occur in the process of implementing a construction project can be seen and predicted from the level of urgency of the work items to be carried out, the analysis that will be used to predict the constraints or obstacles that may occur is by analyzing the critical path of the project implementation schedule construction. The use of Microsoft Project is very effective in analyzing data and determining critical paths. Based on the critical path analysis that has been carried out on the construction project schedule for the construction of residential houses, it is found that several work sub-items are on the critical path, especially in preparatory work and structural work, which means that the work sub-item in this work must pay close attention to the implementation process both in terms of resource readiness. human and equipment.